Kajian Perbedaan Warna Jigs Terhadap Hasil Tangkapan Cumi (Loligo sp.) di Perairan Kei, Kabupaten Maluku Tenggara - Erwin Tanjaya; Erna Almohdar (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
The study of difference in the color of the jigs was carried out considering that the squid (Loligo sp.) is one of the marine biological resources with important economic value. Catching squid carried out by fishermen so far is still traditional because the method of catching is done by using a petromax lamp and using spear fishing gear. Jigs are one type of modern fishing gear that has been modified as artificial bait in catching squid. The color of the jigs is also one of the success factors in getting the catch. The objectives of this research are; determine the color of the best jigs and determine the effective time in squid fishing operations. This research was conducted using an experimental method, namely the experimental design in the form of a randomized block design (RAK) with treatment (t) namely different colors of jigs, namely; Yellow, blue, green and red jigs were assembled randomly on 4 fishing rods with an operating time interval of 3 hours. The results showed that the catch of squid to the color jigs, namely the red jigs color obtained the most catches of 40 fish, the yellow color 21 fish, the green color 13 tails and the blue color 6 fish were the lowest catches while the fishing operation time with the most catches was at at 21.00-24.00 as many as 36 fish followed by time at 24.00-03.00 as many as 22 fish while the time at 18.00-21.00 and 03.00-06.00 were the smallest catches of 11 fish each. The results of this study are expected to provide benefits for squid fishing communities in the waters of the Rossenberg Strait to increase catches.